The COSTA Study: Sternal Closure in High-Risk Patients - A Prospective Randomized Multicenter Trial - Leinberger, Tetyana; Heilmann, Claudia; Sorg, Stefan; Mueller, Matthias; Kueri, Sami; Schmoor, Claudia; Siepe, Matthias; Beyersdorf, Friedhelm (The Thoracic and Cardiovascular Surgeon, 2018)
Background Median sternotomy in patients with risk factors for wound healing is associated with high rates of postoperative wound infections and sternum instability.Methods A total of 338 patients with elective first median sternotomy and at least four predefined risk factors were randomized between Sternal Talon (Gebrüder Martin GmbH & Co. KG—KLS Martin Group, Tuttlingen, Germany) and wire cerclage. The primary end point was mediastinitis and/or sternal instability within 30 ± 5 days, and the secondary end points were mediastinitis and/or sternal instability within 60 ± 5 days; incidence of pneumonia during hospitalization within the first 30 (±5) days and chest pain intensity.Results The primary end point was reached in 10 Sternal Talon and 7 wire cerclage patients (6.2 vs. 4.7%, odds ratio [OR]: 1.3, 95% confidence interval [CI]: 0.5–3.6, p = 0.57) from 338 randomized patients. Sternal Talon group, n = 170 patients versus wire cerclage group, n = 168 patients. The differences between treatment groups with regard to the incidence of mediastinitis/sternum instability within the first 60 (±5) days after the primary sternum closure and the incidence of pneumonia during the hospitalization within the first 30 (±5) days were not statistically significant, either. We observed comparable rates of superficial surgical site infection (SSI) in Sternal Talon and wire cerclage patients (16.1 vs. 12.1%, OR: 1.4, 95% CI: 0.7–2.7, p = 0.31).Conclusion According to these data, there is no statistically significant difference between Sternal Talon closure and wire cerclage in reducing the incidence of mediastinitis and superficial SSI after primary closure of median sternotomy in high-risk patients.
Keywords: mediastinitis; sternal closure; high-risk patients; sternotomy